Photodynamic Therapy as a Desirable Approach in the Treatment of Colorectal Cancer, with Special Focus on Photodynamic Nanotherapeutics in Immunotherapy - Mollazadeh, Samaneh; Mehrabadi, Shima; Hassanian, Seyed Mahdi; Mobarhan, Majid Ghayour; Ferns, Gordon A.; Khazaei, Majid; Avan, Amir (Current Medicinal Chemistry, 2025)
Colorectal cancer (CRC) is one of the most prevalent malignancies worldwide; however, there is not a convincing treatment for this disease. Limitations of conventional CRC therapies force scientists to develop novel treatment concepts for both primary care alongside adjuvant therapy. Photodynamic therapy (PDT) has been introduced as a promising therapeutic procedure for CRC mediated through theranostic principle in which special dyes, photosensitizers (PSs), are excited by near-infrared (NIR) and visible light. Recent studies showed that PDT has synergistic effects in combination with chemotherapy or immunotherapy in the treatment of CRC patients. Of note, nanoformulation of PS or immunotherapeutic agents could augment the PDT effectiveness. In this review, we summarize PDT application in CRC management with a special focus on the nanoparticles-based delivery system from the perspective of targeting deeper CRC and increased PDT efficiency, which could provide a desirable approach for clinical translation.
Keywords: immunotherapy